High flow nasal cannulae for acute viral bronchiolitis in young infants: evidence-based medicine is underway to define target populations and optimal flows - Cambonie, Gilles; Pons-Odena, Marti; Baleine, Julien; Milési, Christophe (Journal of Thoracic Disease, 2017)
Over the last decade, high flow nasal cannulae (HFNC) have increasingly been used for oxygen delivery in neonatology departments, gradually replacing nasal continuous positive airway pressure (nCPAP).